Counting the Cost: Driving the Emergence of Decision-Making Behaviour on Competitiveness Brand - Abadi, Rahmat Riwayat; Musa, M. Ichwan; Haeruddin, M. Ilham Wardhana; Abadi, Ridfan Rifadly; Mustafa, Muh. Yushar (Universitas Muhammadiyah Palembang, 2024)
Consumers of skincare products pay more attention to safety and comfort before deciding to make a purchase. For these personal needs, consumers look for skincare products with a brand image and high quality. This research aims to determine the influence of brand image variables on purchasing decisions through switching costs for consumers who buy Somethinc skincare products. The method used in the research is a descriptive method with a quantitative approach. This research was carried out on Somethinc skincare users in the city of Makassar. The research sample was 100 respondents and sampling used a non-probability sampling method. The sampling technique in this research used purposive sampling. The data collection technique used was a questionnaire. The data analysis method used is using structural equational modeling with the help of the Smart-PLS version 3 application. The research results show that brand image influences purchasing decisions, switching costs influence purchasing decisions, and brand image influences purchasing decisions through switching costs.